Performance testing of HP 37732A datacom / telecom analyzer / Awang Mokhtar Mohamad - Mohamad, Awang Mokhtar (1998)
Bit error rate ( BER) testing can be used to determine the performance level of a circuit. For this project , a HP 37732A Datacom / Telecom Analyzer is used for making BER measurement by using the RS - 23 2C interface of Personal Computer . By using the Voice Modem ( VM 24 Eiectronica Venetta, Italy ), the performance of the transmission is studied in terms of Bit Error Rate ( BER ) , Modulation type and Signal speed.